Fabrication and characterization of woven kenaf/bamboo mat fiber-reinforced epoxy hybrid composites - Ismail, Ahmad Safwan (2018)
Research on natural fiber as reinforcement in polymer composite has increased in the past few years. Natural fiber reinforced polymer composite poses high strength and is lightweight. Besides that, production of natural fiber as reinforcement requires less energy compared to synthetic fiber. In this study, kenaf and bamboo were used as reinforcements while epoxy was used as matrix. A preliminary study was conducted to choose suitable bamboo preparation between bamboo mat, bamboo fabric and bamboo powder for further study on fabrication and characterization of kenaf/bamboo hybrid composites. Bamboo, kenaf, and bamboo/kenaf hybrid composites were fabricated by hand lay-up method. In preliminary work, chemical composition of fibers, tensile, impact and morphological properties of bamboo mat, bamboo fabric, bamboo powder and woven kenaf reinforced epoxy composites were carried out. Following this, bamboo mat was chosen as reinforcement for further study on fabrication of kenaf/bamboo hybrid composites. Hybrid composites of woven kenaf/bamboo mat with different weight ratios of kenaf: bamboo in 70:30, 50:50 and 30:70 were made, Woven kenaf and bamboo mat reinforced epoxy composites were also made as control samples to compare properties with hybrid composites. The effect of hybridization of bamboo mat on mechanical, vibration, sound absorption and morphological properties of woven kenaf/epoxy composites were studied. Hybridization of woven kenaf with bamboo mat improved the mechanical properties of hybrid composites. Hybrid composite with ratio 50:50 showed the highest improvement on tensile strength (55.18 MPa) and modulus (5.15 GPa), elongation at break (2.42 mm), flexural strength (99.41 MPa) and modulus (6.12 GPa) and impact strength (45.06 J/m). Analysis of morphological properties of the samples were carried out using scanning electron microscopy (SEM) to observe fracture behavior and fiber pull out of the tensile fracture sample. Acoustic properties of woven kenaf, bamboo mat and kenaf/ bamboo hybrid composites analysis was conducted according to ISO 10534-2:2001. Sound absorption coefficients of composites were measured in two conditions: without air gap and with air gap (10, 20, 30 mm). Sound absorption coefficients for testing without air gap were less than 0.5. Introducing air gap improved the sound absorption coefficient. Density, void content, water absorption and thickness swelling of the composite were determined. Hybridization of kenaf fiber with bamboo fiber has increased density while void content, water absorption and thickness swelling decreased. Hybrid composite of woven kenaf/bamboo mat with ratio 50:50 showed excellent overall properties in comparison to other hybrid composites. We concluded that woven kenaf/bamboo mat hybrid composites possess sufficient strength and modulus which is suitable for production of crash box and food tray tables.